A study on the impact of innovation on the performance of Singapore logistics firms - Lau, Josephine Yi Lan (2018)
Innovation is one of the key determinants to improve performance, with the increasing demands of customers and the rapidly changing market it is impossible to survive without innovating. This project will discuss on the positive impacts of innovation on the performance of Singapore logistics firms in the context of Healthcare logistics. Surveys and interviews were conducted to understand more about innovations in the industry and individual stakeholders’ views on the role of innovation. From our survey findings, we identified that companies are willing to invest in innovation. External stakeholders such have customers have more influence on whether an organisation will choose to innovate as compared to internal stakeholders. Another motivation for innovation is improvement in processes, companies will invest in innovations according to their needs. It is important that the innovation is a strategic fit to achieve improvement in performance. Innovations in logistics firms were identified and analysis was done to evaluate the impact on performance brought about by these innovations. The analysis was done with a balanced perspective in mind. In the context of Healthcare logistics, traceability and accuracy is essential. It is proven in our analysis that innovations will be able to assist in improving performance in these areas. Generally, there is still a lack of motivation to innovate due to the low profit margins. However, with the government pushing for innovation there is some attempts by firms to innovate. From the analysis, there is innovation in the industry, but it is important that companies invest in innovations that is a strategic fit with organisational goals to achieve improvement in performance.